Frost-acclimation of photosynthesis in overwintering Mediterranean holm oak, grown in Central Europe - Pflug, Ellen; Brüggemann, Wolfgang (International Journal of Plant Biology, 2012)
As a consequence of global change, forestry in Central Europe has to expect and be prepared for an increase of hot and dry summers in the near future. In two model plantations of the Mediterranean holm oak (Quercus ilex L.) in Central Europe (Rhine-Main basin) we tested its potential as a future forestry tree for drought-threatened stands by studying its overwintering strategy under harsh winter conditions. During prolonged frost periods, chronic photoinhibition was developed, which lasted until the end of the frost period. Nearly all plants survived minimum temperatures of - 16 to -18°C and their photosynthetic apparatus recovered completely during late winter. A detailed study of the temperature dependence of chlorophyll (chl) fluorescence parameters of the OJIP test revealed statistically significant correlations between minimum temperature and maximum quantum yield of primary photochemistry (Fv/Fm), absorption rate/reaction centre (ABS/RC), dissipation rate/reaction centre (DI0/RC) and electron transport rate/reaction centre (ET0/RC) as well as with the deepoxidation state (DES) of the xanthophyll pigments. The DES correlated with Fv/Fm, ABS/RC, DI0/RC and ET0/RC. It is concluded, that from the point of view of the winter hardiness of the photosynthetic apparatus, Q. ilex should be further investigated as a potential future forestry tree also for very dry and warm stands in Central Europe under the scenarios of climate change.
Keywords: chlorophyll fluorescence; ojip test; xanthophyll cycle

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro - Brüggemann, Wolfgang; Bergmann, Michael; Nierbauer, Kai-Uwe; Pflug, Ellen; Schmidt, Carlo; Weber, Daniel (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.
Keywords: á downregulation of ps; chlororespiration; chlororespiration á photoinhibition á; downregulation of ps II; ii; photoinhibition; Quercus; quercus á winter acclimation; winter acclimation

Photosynthesis studies on European evergreen and deciduous oaks grown under Central European climate conditions: II. Photoinhibitory and light-independent violaxanthin deepoxidation and downregulation of photosystem II in evergreen, winter-acclimated Euro (Trees, 2009)
In the context of the search for future forestry species in Central Europe under climate change scenarios, the evergreen Mediterranean Quercus taxa Q. ilex ssp. ilex and Q. suber and the semideciduous hybrids. Q. 9 turneri and Q. 9 hispanica were studied in relation to their photochemical efﬁciency of photosystem II and to the activity of the xanthophyll cycle under Central European winter conditions. The evergreen taxa were remarkably insensitive to winter stress in the ﬁeld and reacted towards frost periods with the phenomenon of ‘‘chronic photoinhibition’’, i.e. a decrease in pre-dawn Fv/Fm and an increase in the deepoxidation state of the xanthophylls. Under dark and warmer conditions (room temperature), winter-acclimated leaves of the evergreen taxa except for Q. 9 turneri produced zeaand antheraxanthin and decreased Fv/Fm, possibly by creation of a chlororespiratory pH-gradient. It is suggested that the ability for dark violaxanthin deepoxidation may contribute to the winter hardiness of the evergreen taxa.